Hematological Indices in Portal Hypertension: Cirrhosis versus Noncirrhotic Portal Hypertension - Sahin, Abdurrahman; Artas, Hakan; Tunc, Nurettin; Yalniz, Mehmet; Bahcecioglu, Ibrahim Halil (Mdpi, 2018)
Portal hypertension (PHT) leads to several alterations on hematological indices (HI). The aim of the study is to investigate the differences in HI between cirrhotic subjects and subjects who have noncirrhotic PHT (NCPHT). This retrospective study included 328 patients with PHT (239 cirrhosis and 89 NCPHT). Demographic and clinical features, endoscopic and radiological findings, and HI including neutrophil to lymphocyte ratio (NLR) at the time of PHT diagnosis were recorded. Severity of cirrhosis was assessed according to the Child-Turcotte-Pugh (CTP) classification and Model for End-Stage Liver Disease (MELD) scores. Hematological abnormalities were found in 92.5% of cirrhotic patients and in 55.1% of patients with NCPHT (p < 0.001). While thrombocytopenia was the most common HI in patients with cirrhosis, anemia was the most prevalent HI in NCPHT group. In the cirrhotic group, the NLR was the only parameter to differentiate each CTP group from two others. The NLR value increased with the severity of cirrhosis (2.28 +/- 0.14 in CTP-A, 2.85 +/- 0.19 in CTP-B and 3.26 +/- 0.37 in CTP-C). The AUROC of NLR was 0.692 for differentiating compensated cirrhotic patients from decompensated. Hematological abnormalities are more prevalent and more severe in cirrhotic patients compared to patients with NCPHT. NLR may be used to assess the severity of cirrhosis.
Keywords: hematological indices; portal hypertension; cirrhosis; noncirrhotic portal hypertension; neutrophil to lymphocyte ratio